2020
DOI: 10.1177/1120672120937674
|View full text |Cite
|
Sign up to set email alerts
|

Suprasellar meningioma presenting with glaucomatous type cupping

Abstract: Purpose: To describe a case of a suprasellar meningioma compressing the chiasm from below and producing a unilateral fascicular (nasal) visual field defect that mimicked glaucomatous cupping. Case report: A 78-year-old man presented with painless, progressive, unilateral arcuate visual field defect. He was diagnosed with “normal tension glaucoma” based on an asymmetric cup to disc ratio. Despite treatment with anti-glaucoma drops, the visual field defect progressed. Neurophthalmic evaluation was consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In these cases, the clinician may inadvertently miss a compressive intracranial cause and focus attention on an intraocular cause of field defect. Interestingly, an expanding mass in the sellar region may asymmetrically compress the chiasm or compress the distal optic nerve(s) before the chiasm producing a true monocular visual field defect with a fascicular defect [ 11 , 12 ]. To add confusion in the clinical evaluation of these cases, one has to consider that in compressive optic neuropathy, the optic nerve may appear normal initially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the clinician may inadvertently miss a compressive intracranial cause and focus attention on an intraocular cause of field defect. Interestingly, an expanding mass in the sellar region may asymmetrically compress the chiasm or compress the distal optic nerve(s) before the chiasm producing a true monocular visual field defect with a fascicular defect [ 11 , 12 ]. To add confusion in the clinical evaluation of these cases, one has to consider that in compressive optic neuropathy, the optic nerve may appear normal initially.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, visual function (color and acuity) is usually preserved in glaucoma until later stages because of the relative sparing of the papillomacular bundle [ 15 , 16 ]. However, even in compressive optic neuropathy, visual acuity may be normal initially [ 11 ]. The clinician may thus face the case of a fascicular monocular visual field defect with normal visual acuity and an unremarkable (or cupped) optic disc with not so much pallor, and easily led to diagnose an NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compression of the intracranial optic nerve up to the junction of the anterior optic chiasm can produce accurate visual field defects resembling glaucoma with sparing of central vision. 12…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compression of the intracranial optic nerve up to the junction of the anterior optic chiasm can produce accurate visual field defects resembling glaucoma with sparing of central vision. 12 Clinicians should be aware of these distinguishing and differentiating features of non-glaucomatous optic neuropathy and consider neuroimaging to exclude a compressive lesion mimicking glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Compressive optic neuropathies causing cupping have been observed in patients with pituitary adenomas, 6 , 7 , 16–20 aneurysms, 21–24 craniopharyngiomas 19 , 25 and meningiomas. 16 , 17 , 19 , 26 , 27 Bianchi-Marzoli et al 28 performed a masked measurement of the optic discs of 29 patients with compressive optic neuropathies and 20 age-matched controls. This study found a significantly larger cup-to-disc ratio (0.37) for eyes with compressive optic neuropathies than for control eyes (0.10).…”
Section: Conditions That Mimic Glaucomatous Cuppingmentioning
confidence: 99%